OBESITY TO THE LUNG - FORCE VITAL CAPASITY (FVC) RELATION AT THE STUDENTS OF SMA NEGERI 2 BANDAR LAMPUNG - Dwika, Dicky Aditya; Berawi, Khairunnisa; -, Susianti; -, Muhartono (Majority, 2015)
Abstract Obesity or too-fat is an over relative human weight condition caused by accumulation of nutrition, especially carbohydrate and fat. Based on WHO data in 2006, there was 1.6 billion adult people in the world was in overweight condition and unless than 400 millions from that was in obesity condition. In Indonesia, based on Basic Health Research (Riskesdas) data in 2007, national prevalence in general obesity at >15 years old inhabitants was 10.3% (13.9% male, 23.8% female). Obesity, especially central obesity (abdominal) is associated with many metabolism disruption and illness. Besides that, obesity (especially morbid type) is also associated with many types of human respiratory disruption. The aims of this research were to find if there’s “related” or “unrelated” condition between obesity and Lung–Force Vital Capacity (FVC) at the studens of SMA N 2 Bandar Lampung. The research type that used is analitic descriptive research with cross-sectional research program. Respondents are counted 92 male and female students, data was analyzed univariate and bivariate using chi-square exam. The result of this research showed that 6.52% respondents were in obese-BMI. The result of chi-square statistic exam shows p=0.076 (p<0.1) which means that there was different value between respondents with obese- BMI and respondents with nonobese- BMI. Keywords: obesity, BMI, forced vital capacity (fvc) Abstrak Obesitas atau kegemukan adalah suatu keadaan yang melebihi dari berat badan relatif seseorang, sebagai akibat penumpukan zat gizi terutama karbohidrat dan lemak. Menurut data WHO tahun 2006, terdapat 1,6 miliar orang dewasa di seluruh dunia mengalami berat badan berlebih (overweight), dan sekurangkurangnya 400 juta diantaranya mengalami obesitas. Di Indonesia, menurut data Riset Kesehatan Dasar (Riskesdas) tahun 2007, prevalensi nasional obesitas umum pada penduduk berusia >15 tahun adalah 10,3% (laki-laki 13,9%, perempuan 23,8%). Obesitas, khususnya obesitas sentral (abdominal), berasosiasi dengan sejumlah gangguan metabolisme dan penyakit. Selain itu, obesitas (khususnya tipe morbid) juga berasosiasi dengan beberapa jenis gangguan pernapasan. Tujuan dari penelitian ini adalah untuk mengetahui ada tidaknya hubungan antara obesitas terhadap kapasitas vital paksa (Force Vital Capacity /FVC) paru pada siswa Sekolah Menengah Atas (SMA) Negeri 2 Bandar Lampung. Jenis penelitian yang digunakan adalah penelitian deskriptif analitik dengan rancangan penelitian cross sectional. Jumlah responden sebanyak 92 orang siswa berjenis kelamin laki-laki dan perempuan, data dianalisis univariat dan bivariat menggunakan uji chi-square. Hasil penelitian menunjukkan 6,52% responden memiliki BMI obese. Hasil uji statistic chi-square diperoleh p=0,076 (p<0,1) yang artinya terdapat perbedaan nilai kapasitas vital paksa yang bermakna antara responden dengan BMI obese dan responden dengan BMI non-obese. Kata kunci: BMI, kapasitas vital paksa (forced vital capacity/fvc), obesitas